Recent Advances of Neural Network Models and Applications Proceedings of the 23rd Workshop of the Italian Neural Networks Society (SIREN), May 23-25, Vietri sul Mare, Salerno, Italy - Bassis, Simone; Esposito, Anna.; Morabito, Francesco Carlo; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2014)
This volume collects a selection of contributions which has been presented at the 23rd Italian Workshop on Neural Networks, the yearly meeting of the Italian Society for Neural Networks (SIREN). The conference was held in Vietri sul Mare, Salerno, Italy during May 23-24, 2013. The annual meeting of SIREN is sponsored by International Neural Network Society (INNS), European Neural Network Society (ENNS) and IEEE Computational Intelligence Society (CIS). The book – as well as the workshop-  is organized in two main components, a special session and a group of regular sessions featuring different aspects and point of views of artificial neural networks, artificial and natural intelligence, as well as psychological and cognitive theories for modeling human behaviors and human machine interactions, including Information Communication applications of compelling interest.  .
I Algorithms -- II Signal Processing -- III Applications -- IV Special Session on \Social and Emotional Networks for Interactional Exchanges.
Keywords: Computational intelligence; Artificial intelligence; Computational Intelligence; Artificial Intelligence